(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
In the context of globalization, the role of simultaneous interpretation as a means of interlanguage communication is becoming particularly important. Real-time translation requires not only high language skills, but also a deep understanding of the differences between the structure, semantics, and pragmatics of languages. This article is devoted to the analysis of the features of comparative translation between English and Uzbek in the context of simultaneous interpretation. The main grammatical, lexical, syntactic, and cultural differences are considered, and strategies for overcoming typical difficulties faced by translators are proposed. The material is based on theoretical works in the field of translation linguistics and includes specific examples of translation from English to Uzbek and vice versa.